Evaluation of neutron fluence in the treatment room and along the maze of an 18 MV linear accelerator - Siltzovalis, G.; Papadopoulos, K.; Savva, M. I.; Vasilopoulou, T.; Georgolopoulou, P.; Karaiskos, P.; Kalef-Ezra, J.; Stamatelatos, I. E. (HNPS Advances in Nuclear Physics, 2019)
Neutron fluence and dose equivalent rate in the treatment room and along the maze of an 18 MV medical linear accelerator was evaluated using Monte Carlo code MCNP5. Scope of the study was to test the hypothesis that a simple accelerator head model can adequately estimate the neutron fluence in the treatment room and along the maze without the requirement of a detailed modeling of the complex accelerator head configuration. The accelerator head was modeled either as a spherical cell source of 10 cm in radius or as a point source in the centre of a spherical cell of 10 cm internal and 20 cm external radious,  both made of tungsten. The calculations were compared against measurements performed using gold and indium activation foils. A good agreement between calculated and experimental results was observed in the treatment room. However, the calculations at the maze entrance overestimated the neutron fluence by a factor of 3. The results of the study contribute towards the development of a simple and computationally cost effective methodology for the calculation of neutron dose in the treatment room and the maze of high energy medical accelerators providing a representative simulation of the complex accelerator, bunker and maze configurations that cannot be described by presently used analytical expressions.